Dynamic Source Distribution and Emission Inventory of a Persistent, Mobile, and Toxic (PMT) Substance, Melamine, in China - S. Zhang; J. Chen; Z. Wang; C. Chen; Chen, A.; Q Jing; J Liu* (Environmental Science & Technology (ES&T), 2023)
Persistent, mobile, and toxic (PMT) substances are affecting the safety of drinking water and are threatening the environment and human health. Many PMT substances are used in industrial processing or consumer products, but their sources and emissions mostly remain unclear. This study presents a long-term source distribution and emission estimation of melamine, a high-production-volume PMT substance of emerging global concern. The results indicate that in China, approximately 1858.7 kilotonnes (kt) of melamine were released into the water (∼58.9%), air (∼27.0%), and soil systems (∼14.1%) between 1995 and 2020, mainly from its production and use in the decorative panels, textiles, and paper industries. The textile and paper industries have the highest emission-to-consumption ratios, with more than 90% emissions per unit consumption. Sewage treatment plants are the largest source of melamine in the environment for the time being, but in-use products and their wastes will serve as significant melamine sources in the future. The study prompts priority action to control the risk of PMT substances internationally.